A comparative analysis of outcomes of root canal therapy for pediatric medicaid beneficiaries from New York State - Burns, Lorel E.; Gencerliler, Nihan; Terlizzi, Kelly; Wu, Yinxiang; Solis-Roman, Claudia; Gold, Heather T. (Frontiers in Oral Health, 2022)
Objectives This study investigated differences in the provision of root canal therapy and outcomes in a publicly insured cohort of children and adolescents. Methods New York State Medicaid administrative claims from 2006 to 2018 were analyzed. Enrollees aged 6–18 were included in the study if they had initial non-surgical root canal therapy (NSRCT), in the permanent dentition, that allowed for at least 1 year of post-treatment follow-up. Descriptive analyses, multivariable logistic regression, and multivariable Cox proportional hazard models were used to examine the association between demographic variables (gender, age, race/ethnicity, and area-based factors) and dental treatment provision and outcomes. Results Male gender was associated with having more than one initial NSRCT (adjusted odds ratio (aOR) = 1.06; 95% confidence interval (CI) = 1.02–1.10), as was rurality (aOR = 1.15; 95% CI = 1.06–1.24). Black/African American (AA) and Hispanic children were less likely than non-Hispanic white children to have multiple NSRCTs (aOR = 0.88; 95% CI = 0.83–0.93 and aOR = 0.78; 95% CI = 0.74–0.83). Being older or female conferred a lower hazard of an untoward event (aHR = 0.93; 95% CI = 0.92–0.94 and aHR = 0.86; 95% CI = 0.81–0.91). Compared to non-Hispanic white children, Hispanic and Black/AA children had a higher risk of untoward event (aHR = 1.31; 95% CI = 1.21–1.41 and aHR = 1.55; 95% CI = 1.43–1.67) while children of Asian descent had a lower incidence after initial NSRCT (aHR = 0.79; 95% CI = 0.71–0.88). Conclusion Race/ethnicity was the strongest demographic predictor of provision of initial non-surgical root canal therapy, subsequent placement of a permanent restoration and the occurrence of an untoward event after NSRCT in this cohort.